Tools and talk: an evolutionary perspective on the functional deficits associated with amyotrophic lateral sclerosis. - Eisen, A; Turner, M; Lemon, R (2014)
We propose that amyotrophic lateral sclerosis (ALS), and frontotemporal dementia may be viewed as a failure of interlinked functional complexes having their origins in key evolutionary adaptations. We discuss how hand-arm function, locomotion, brainstem function (involving vocalization/speech, swallowing and breathing), and cognitive impairment share complex, interdependent evolutionary adaptations that can be traced back several million years. Fine movements of the hand facilitated tool-making and use enhanced by development of bipedalism. Development of the larynx and integration of respiratory control were central to vocalization, which when combined with gesture are intermediary to human language. These adaptations were accompanied by progressive encephalization, with development of Theory of Mind to facilitate socialization. The varied clinical phenotypes of ALS can thus be understood in the context of inter-related functional complexes that subserve "Tools and Talk"; they have a long evolutionary history and are related to specific developmental neural and gene networks.